2018
DOI: 10.4014/jmb.1801.01013
|View full text |Cite
|
Sign up to set email alerts
|

Deastringent Peel Extracts of Persimmon (Diospyros kaki Thunb. cv. Cheongdo-Bansi) Protect Neuronal PC-12 and SH-SY5Y Cells against Oxidative Stress

Abstract: The peel of astringent persimmon (Diospyros kaki Thunb. cv. Cheongdo-Bansi) is a by-product of dried persimmon (gotgam). We investigated if deastringent peel extracts of persimmon cv. Cheongdo-Bansi had antioxidative and neuroprotective properties. Two different extracts were prepared: thermally and nonthermally treated persimmon peel extracts (TPE and NTPE, respectively). Both TPE and NTPE were fractionated sequentially in n-hexane, chloroform, ethyl acetate, n-butanol, and water. The TPE and NTPE ethyl aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…The total phenolic contents of the KPP samples with regards to the heating temperature were ordered as follows: KPPH > KPPM > KPPL; the total phenolic contents of the KPP samples with regards to the heating time were ordered as follows: 1 h > 2.5 h > 2 h > 1.5 h > 0.5 h. Higher temperature conditions showed more total phenol contents and the highest total phenolic content was found in KPP samples prepared by heating treatment at 90℃ and 1 h (KPPH-1h) (1,000.2 ± 72.4 ㎎•GAE/100g). This is similar to the result of the study by Jeong et al (2018), who demonstrated that the total phenolic content of water-soluble extracts of Cheongdo-Bansi peels was between 1,060.3 ± 126.3 ㎎•GAE/100g. Interestingly, in case of all three heating temperatures, an extracting time of 1 h showed relatively higher total phenolic contents, compared to other extracting conditions.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The total phenolic contents of the KPP samples with regards to the heating temperature were ordered as follows: KPPH > KPPM > KPPL; the total phenolic contents of the KPP samples with regards to the heating time were ordered as follows: 1 h > 2.5 h > 2 h > 1.5 h > 0.5 h. Higher temperature conditions showed more total phenol contents and the highest total phenolic content was found in KPP samples prepared by heating treatment at 90℃ and 1 h (KPPH-1h) (1,000.2 ± 72.4 ㎎•GAE/100g). This is similar to the result of the study by Jeong et al (2018), who demonstrated that the total phenolic content of water-soluble extracts of Cheongdo-Bansi peels was between 1,060.3 ± 126.3 ㎎•GAE/100g. Interestingly, in case of all three heating temperatures, an extracting time of 1 h showed relatively higher total phenolic contents, compared to other extracting conditions.…”
Section: Resultssupporting
confidence: 91%
“…Also, the peel of persimmon is known to have a higher total phenolic content and antioxidant capacity than the pulp (Kim et al, 2010;Park et al, 2014;Lee et al, 2015). Peels from dried persimmons may be new functional materials, but only a few studies have investigated whether these peels have biological activity (Seo et al, 2000;Kawakami et al, 2010;Jeong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants are important molecules that provide protection against the deleterious effects of ROS, and are therefore frequently used in the medicinal and food industries. The interest in identifying natural antioxidants from plants, seaweed, microorganisms, and other materials has been increasing recently [30][31][32].…”
Section: Analysis Of Pee Composition Using Hplcmentioning
confidence: 99%
“…Therefore, the ameliorating effect on the cholinergic system was confirmed to assess the ACh content and inhibitory effect of AChE (Figure 2). According to a previous study, the ethyl acetate fraction of immature persimmon peel containing quercetin and quercetin aglycone such as quercetin 3-O-galactoside, quercetin-3-O-galactoside-2 -Ogallate and quercetin-3-O-glucoside inhibits the activity of AChE and butyrylcholinesterase (BuChE) [51]. In addition, the gallic acid contained in IPEE improves the synaptic strength and decreases the size of Aβ plaques in cerebral tissues through an improvement effect on synaptic damage induced by Aβ peptides [52].…”
Section: Discussionmentioning
confidence: 99%